Design of the Android-based Kartu Menuju Sehat (KMS) Application as a Toddler Growth and Development Monitoring - Wulandari, Fitria; Ratna Wulan, Widya; Kurniadi, Arif; Setiono, Oki (International Journal of Health Literacy and Science, 2024)
The growth and development of infants and toddlers can be regularly monitored using KMS (Card Towards Health). Monitoring growth and development has been carried out but is still manually in the KMS book. The research aims to develop an information system that supports monitoring toddlers' growth and development status. System development uses the system development life cycle (SDLC), and system trials are used to determine user acceptance of the developed application. The system development method is carried out in three stages: design, development, and implementation. The results of the trial show that the system developed provides results that meet user needs. The system test results show that the application can give output information on monitoring toddlers' growth and development status, which can be displayed in graphic form, Excel, or PDF format. Nomor Induk Kependudukan (NIK) data was added to compare it with other health applications in the developed system.